Parietal thoracic, diaphragmatic and intercostal hernia of traumatic origin - Piñeyro, Alberto; Taroco, Luis; Misa, Carlos; Hernández, Walter (Cirugía del Uruguay, 1986)
Presents a case of right traumatic diaphragmatic hernia also accompanied with a intercostal opening throug wlch small intestina and colon passed into the righl hemithorax and subcutaneous cellular (lissue). Briel revision of !he subject, its physiopathological and clínical elements in particular.